HAMBATAN PARATE EKSEKUSI HAK TANGGUNGAN SEBAGAI PENYELESAIAN KREDIT MACET DI PT. BANK TABUNGAN PENSIUNAN NASIONAL TBK - , INAS FEBRIANA SUPARMAN, Taufiq El Rahman, S.H, M.Hum ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research aims to find out and analyse the effort made by PT. Bank Tabungan Pensiunan Nasional Tbk in regard to the unsold collateral object through parate execution of the mortgage and discusses the effort made by PT. Bank Tabungan Pensiunan Nasional Tbk in facing the resistance or denial of the debtor or the third party during the implementation process of parate execution of the mortgage This research use empirical juridical method, which is by doing research in order to collect primary data related to field research and also supported with library research to collect secondary data. The library research obtained from reading and learning from literature and relevant researches, whereas field research obtained through interview with interviewees and respondents. The results of this study show that the effort made by PT. Bank Tabungan Pensiunan Nasional Tbk in response to the unsold collateral object through parate execution of the mortgage is to conduct periodic auctions using the auctions limit reduction strategy. Secondly, the effort made by PT. Bank Tabungan PensiunanNasionalTbkin facing the resistance or denial of the debtor or the third party during the implementation process of parate execution of the mortgage is to follow the judicial proceedings and defend for the interests of the legal which may put the bank at risks with the cessation of the auction process and inhibit debt settlement.